Influencia del sismo de Golfito del 30 de julio de 2002 (Mw 6,2) sobre una prueba de bombeo en el acuífero confinado del sitio de presa del P.H. Pirrís, Costa Rica - Vargas, Asdrúbal G. (2016)
In order to determine the hydrogeological parameters of the fractured confined aquifer founded in the dam site of the Pirrís hydroelectric Power, a pumping test was carry out during 2560 minutes with an average flow rate of 1,9 l/s, using a submersible pump of 5,6 kW. Approximately 420 minutes after the beginning of the pumping test a earthquake with a magnitude of 6.2 MW with an epicenter near the town of Golfito (133,7 km far away), cause a significant change in the drawdowns values observed in four piezometers produced by the pumping in the well. After the event a recovery of the groundwater level in all piezometers were recorded, although the well continued with the extraction process. Using the recorded level and the time is possible the identification in a graph of five phases. Phase 1 corresponds to a drawdown of groundwater level caused by pumping with a 6-hour period; the second phase shows a sharp recovery as a result of the earthquake. The third phase is related to stabilization levels after the earthquake, however then a new level recovery phase occurs due to several aftershocks and finally another period of small drawdown is presented. After the test the data were reviewed to determine the effect of various parameters. For example partial penetration of the well, and the dip of the aquifer. From this preliminary analysis it was concluded that these factors did not influence the traditional method for the estimation of hydrodynamic parameters, therefore it was decided to analyze the data by the method of Theis and Moench for confined and fractured aquifers respectively.